Systematic Mining of Gene Co-Expression Network Suggesting a New Drug Repositioning for the Effective Treatment of Duchenne Muscular Dystrophy: Drug repositioning for the effective treatment of Duchenne Muscular Dystrophy - Derakhshani, Afshin; Moosavi, Maryam; Nasseri, Saeed; Miri-Moghaddam, Ebrahim; Safarpour, Hossein; Baradaran, Behzad (Iranian Journal of Pharmaceutical Sciences, 2021)
Duchenne Muscular Dystrophy (DMD) is one of the most common inherited disorders worldwide. As there is currently no absolute treatment, the present systems biology study aimed to propose a new drug repositioning for DMD therapy. A microarray dataset of 16 DMD and 6 control samples were analyzed and 208 differentially expressed genes were screened. Weighted gene co-expression network analysis (WGCNA) algorithm, was applied to obtain co-expressed gene networks for the establishment of transcriptional modules related to clinical and demographic data of DMD patients. Results indicated that a maximum of 11 co-expression modules is present in datasets with a varying number of genes. Turquoise module with 3334 genes was strongly correlated with collagen fibril organization as a positive regulator in DMD pathogenesis (r=0.98, p-value=2/00E-15) through which other DMD related hub-genes were identified as COL1A1, FZD10, COL1A2, CRISPLD1, FMO1, COL5A1, COL3A1, COL5A2, TP53I3, PLAGL1, RIPK2, SBF1, MLXIP, CFAP46, and TYRP1. Drug repositioning of the turquoise module identified some candidate drugs which are not presently approved for the treatment of DMD. The targets in the turquoise module indicated that some drugs might greatly affect DMD disease. Furthermore, drug repositioning introduced Zoledronic acid as a potent antagonist for COL1A1.